2010
DOI: 10.1007/s00216-010-4266-7
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading bioluminescent bacterial bioreporter performance by splitting the lux operon

Abstract: Bioluminescent bacterial bioreporters harbor a fusion of bacterial bioluminescence genes (luxCDABE), acting as the reporting element, to a stress-response promoter, serving as the sensing element. Upon exposure to conditions that activate the promoter, such as an environmental stress or the presence of an inducing chemical, the promoter::reporter fusion generates a dose-dependent bioluminescent signal. In order to improve bioluminescent bioreporter performance we have split the luxCDABE genes of Photorhabdus l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 33 publications
1
18
0
1
Order By: Relevance
“…Here, although the reporter system is functional when all genes are located in a single operon, some substrate limitations can occur that limit the linearity of the reporter system. Recent studies have shown that this limitation is circumvented by independent and constitutive expression of the substrate-producing genes luxC , D , E and by only controlling expression of the luciferase-encoding genes by the promoter of interest [20]. …”
Section: Bacterial Luciferasesmentioning
confidence: 99%
“…Here, although the reporter system is functional when all genes are located in a single operon, some substrate limitations can occur that limit the linearity of the reporter system. Recent studies have shown that this limitation is circumvented by independent and constitutive expression of the substrate-producing genes luxC , D , E and by only controlling expression of the luciferase-encoding genes by the promoter of interest [20]. …”
Section: Bacterial Luciferasesmentioning
confidence: 99%
“…Compared to ?uorescent signals, bioluminescent signals show lower illumination intensity (Troy et al 2004). A number of studies have attempted to increase bioluminescence signals (Chang et al 2004;Yagur-Kroll and Belkin 2011), including those by MEB (Eltzov et al 2009). The technology developed in this study aims at improving this on two fronts; the ?rst, includes optimizing the known silver deposition methodology (Eltzov et al 2009) and the second, enhancing signals of the different bioreporters.…”
Section: Resultsmentioning
confidence: 97%
“…The P. luminescens luxCDABE cassette was also instrumental in a demonstration of an improvement of bioreporter performance by rearranging the lux-CDABE genes and splitting them into two independent functional units: luxAB, coding for the luciferase enzyme, and luxCDE, coding for the reductase complex [27]. The hypothesis that splitting the five-genes operon will be beneficial was driven by three main assumptions:…”
Section: Genetic Manipulations Of Lux Reporting Elementsmentioning
confidence: 99%